Penggunaan Handphone secara Berlebihan dan Pengelolaan Waktu dalam Perspektif Al-Qur'an: Kajian Tafsir Surah Al-'Ashr dan Al-Mu'minun - Wahidatul Husna; Muhammad Jamil (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the impact of excessive mobile phone use on daily activities, productivity, and the effective management of time, examine the perspective of the Qur'an, particularly Surahs Al-'Ashr and Al-Mu'minun, regarding time management and the avoidance of futile (laghw) activities in the context of mobile phone use and formulate ideal, wise, and proportional guidelines for mobile phone use based on the perspectives of these two surahs. This study employed a qualitative method using a library research approach. Primary data were obtained from the Qur'an, specifically Surahs Al-'Ashr and Al-Mu'minun, as well as classical and contemporary Qur'anic commentaries, including Tafsir Al-Misbah, Tafsir Al-Azhar, and Tafsir Ibn Kathir. Secondary data were collected from books, scientific journals, articles, and other relevant scholarly publications. Data were gathered through documentation studies and analyzed using content analysis techniques. The findings indicate that excessive mobile phone use can disrupt daily activities, reduce productivity, decrease the effectiveness of time management, and increase engagement in futile digital activities. The perspective of Surah Al-'Ashr emphasizes the importance of utilizing time through faith, righteous deeds, and mutual encouragement in truth and patience to avoid loss. Meanwhile, Surah Al-Mu'minun highlights that one of the characteristics of successful believers is avoiding futile (laghw) actions. Therefore, mobile phone use should be directed toward activities that promote worship, education, productivity, Islamic propagation (da'wah), and public benefit, accompanied by self-control and proper time management. In this way, technology can serve as a means of achieving success in both worldly life and the Hereafter